Quantitative Proteomic Analysis of Low Linolenic Acid Transgenic Soybean Reveals Perturbations of Fatty Acid Metabolic Pathways. Issue 7 (4th April 2019) - Islam, Nazrul; Bates, Philip D.; Maria John, K. M.; Krishnan, Hari B.; J. Zhang, Zhanyuan; Luthria, Devanand L.; Natarajan, Savithiry S.
Abstract: To understand the effect of fatty acid desaturase gene ( GmFAD3 ) silencing on perturbation of fatty acid (FA) metabolic pathways, the changes are compared in protein profiling in control and low linolenic acid transgenic soybeans using tandem mass tag based mass spectrometry. Protein profiling of the transgenic line unveiled changes in several key enzymes of FA metabolism. This includes enzymes of lower abundance; fabH, fabF, and thioestrase associated with FA initiation, elongation, and desaturation processes and LOX1_5, ACOX, ACAA1, MFP2 associated with β‐oxidation of α‐linolenic acids pathways. In addition, the GmFAD3 silencing results in a significant reduction in one of the major allergens, Gly m 4 (C6T3L5). These results are important for exploring how plants adjust in their biological processes when certain changes are induced in the genetic makeup. A complete understanding of these processes will aid researchers to alter genes for developing value‐added soybeans.